Investigation on Improvement of Surface Roughness Using Rotary Ultrasonic Assisted Machining Technique for Hardened Steel Material / Azlan Ramli...[et al.] - Ramli, Azlan; Raja Abdullah, Raja Izamshah; Abu Bakar, Mohd Hadzley; Kasim, Mohd Shahir; A. Rahman, Muhamad Arfauz; Mohd Zakaria, Muhammad Akmal (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Several challenges are faced by manufacturers producing best surface finish especially for the mould and die applications. In general, most of the mould and die material are made from hardened steel (~40-60 HRc). The high strength of these materials reduced the capability of the conventional machining technique. Poor machined surface and high tool wear rate are among the problems associated with the conventional machining of this material. To overcome these problems, this paper proposed a hybrid machining process by adding an ultrasonic transducer to the normal tooling system namely ultrasonic assisted machining (UAM). Experimental work consisted of a comparison between ultrasonic assisted machining and conventional machining for different parameters namely cutting speed, feed rate and machining depth in order to validate the effectiveness of the proposed technique in improving the surface roughness value for machining hardened AISI D2 material. 2 level factorial design with 3 factors was employed as the technique of design of experiment (DOE). The machining test showed that the presence of rotary ultrasonic assisted vibration significantly improved the machined surface roughness with up to 85% reduction in Ra value compared to the conventional machining process with the same cutting conditions. In addition, the macroscopic observation of machined surface showed that the surface produced from ultrasonic machining was uniform with consistent peak to peak value which improved the surface finish.